Male partner involvement and successful completion of the prevention of mother‐to‐child transmission continuum of care in Kenya. Issue 3 (10th December 2020) - Hampanda, Karen; Helova, Anna; Odwar, Tobias; Odeny, Thomas; Onono, Maricianah; Bukusi, Elizabeth; Turan, Janet; Abuogi, Lisa
Abstract: Objective: To examine the relationship between male partner involvement (MPI) in prevention of mother‐to‐child transmission (PMTCT) activities and successful completion of the PMTCT continuum of care, which remains sub‐optimal in settings with high prevalence of HIV. Methods: A cross‐sectional survey was administered in June–August 2017 to a sample of 200 postpartum Kenyan women with HIV enrolled in a parent trial. Composite PMTCT and MPI variables were created. Descriptive, simple and multivariable regression, and mediation analyses were performed. Results: Of the women, 54% reported successful completion of PMTCT. Depression and internalized HIV stigma were independently associated with lower likelihood of successful completion of PMTCT (adjusted risk ratio [aRR] 0.97; 95% confidence interval [CI] 0.94–0.99; aRR 0.92; 95% CI 0.88–0.98, respectively). Each MPI activity was associated with 10% greater likelihood of successful completion of PMTCT ( P  < 0.05). The relationship between MPI and the successful completion of PMTCT was partially mediated through women's reduced internalized HIV stigma (β −0.03; 95%CI −0.06 to −0.00). Conclusion: Greater MPI in PMTCT activities has direct and indirect effects on women's successful completion of all necessary steps across the PMTCT continuum. Reduced internalized HIV stigma is likely a key mechanism in the relationship. Synopsis: Male involvement is associated with a dose‐response effect on successful completion of the PMTCT continuum of care and is partially mediated through reduced internalized HIV stigma.